2016
DOI: 10.1107/s1600577516007177
|View full text |Cite
|
Sign up to set email alerts
|

Generation of ultra-large-bandwidth X-ray free-electron-laser pulses with a transverse-gradient undulator

Abstract: A new and simple method to generate X-ray free-electron-laser radiation with unprecedented spectral bandwidth above the 10% level is presented. The broad bandwidth is achieved by sending a transversely tilted beam through a transverse-gradient undulator. The extent of the bandwidth can easily be controlled by variation of the beam tilt or the undulator gradient. Numerical simulations confirm the validity and feasibility of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…A sophisticated undulator approach (CHIC) 72 ensures a flexible photon source for experiments, 73,110 and a novel undulator design (APPLE X) allows for easy control over polarization and photon energy 74 . The definition of the three beamlines and their experimental stations is currently in progress in consultation with the SwissFEL user community.…”
Section: Concepts Instruments and Methodsmentioning
confidence: 99%
“…A sophisticated undulator approach (CHIC) 72 ensures a flexible photon source for experiments, 73,110 and a novel undulator design (APPLE X) allows for easy control over polarization and photon energy 74 . The definition of the three beamlines and their experimental stations is currently in progress in consultation with the SwissFEL user community.…”
Section: Concepts Instruments and Methodsmentioning
confidence: 99%
“…Since a standard HGHG configuration usually employs a normal modulator, this simple method may provide a way to operate a PEHG FEL with a standard HGHG configuration. Moreover, we believe that the natural transverse gradient of a normal planar modulator also has the potential of being applied to other purposes of TGUs, such as high-gain X-FELs in diffraction-limited storage rings , the generation of ultra-large-bandwidth X-FELs (Prat et al, 2016) and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The electrons in the so-called 'tilted beam' can be characterized by the transverse offset x in proportion to the longitudinal position s. The coupling between the longitudinal and transverse positions of the particles is normally unwanted in the conventional FEL facilities for the reason that only a fraction of the beam can contribute to the FEL radiation and therefore the corresponding output performance is degraded. However, the recent researches demonstrated that the tilted beam has many important applications, such as production of broad-bandwidth radiation [18,19], generation of ultrashort FEL pulse [20][21][22] and generation of twocolor pulses [23,24] and so on. Such applications can satisfy some specific experimental requirements, for instance, the pump-probe experiments and nonlinear optics experiments.…”
Section: Methodsmentioning
confidence: 99%